دور الاسرة في تكريس التربية الدينية لدى الطفل دراسة ميدانية لعينة من أولياء التلاميذ بمدرسة الشهيد رقيق لخض - معروف وهيبة; اشراف: مامش نجية (جامعة محمد بوضياف المسيلة, 2025)
تهدف الدراسة الحالية إلى الكشف دور الأسرةالجزائرية في تكريسالتربية الدينية لدى الطفل، حيث بلغ حجم العينة 120 وليا، وتم استخدام المنهج الوصفي التحليلي لكونه الأنسب لتحقيق أهداف الدراسة، وقد اعتمدت على أداتين لجمع البيانات، تمثلت الأولى في الاستمارة كأداة رئيسية، والثانية في الملاحظة كأداة مساعدة، وقد شملت الأداة محورين أساسيين هما:محور خاص بمستوى الممارسة، ومحور خاصبأساليب التربية الدينية في الأسرةالجزائرية، وتم التأكد من صدق وثبات الأداة، تم الاعتماد على المقاييس الإحصائية (معامل ألفا كرونباخ ومعامل الارتباط الثنائي لبيرسون)، وقد أظهرت النتائج أن الأداة صالحة للتجريب بناء على القيم المقبولة للثبات والصدق، كما كشفت النتائج النهائية للدراسة أن: - لمستوى تكريسالتربية الدينية في الأسرة علاقة قوية بمستوى التكريسالتربية الدينية. - للأساليب المستخدمة من طرف الأسرة في تكريسالتربية الدينية لدى الطفل علاقة قوية بمستوى التكريسالتربية الدينية. - للسمات الفردية للأبوين (السن، المستوى التعليمي، والمهنة) علاقة ضعيفة بمستوى تكريسالتربية الدينية. - للسمات الفردية للأبوين علاقة ضعيفة بنوعية الأساليب التربوية المستخدمة في تكريسالتربية الدينية. - لنمط الأسرة ونوع الأساليب المتبعة علاقة ضعيفة في تكريسالتربية الدينية. الكلمات المفتاحية: الأسرة الجزائرية، التربية الدينية، أساليب التربوية، الممارسات الدينية، مستوى التكريس الديني. Abstract The currentstudyaims to explore the role of the Algerian family in instillingIslamiceducation in children. The sampleconsisted of 120 parents, and the descriptive-analyticalapproachwasadopted as the mostappropriatemethod to achieve the study’s objectives. Two main toolswereused for data collection: the questionnaire as the primarytool, and observation as a supplementary one. The instrument coveredtwo main dimensions: the level of practice and the methods of Islamicupbringingusedwithin the Algerian family. The validity and reliability of the instrument wereconfirmedusingstatisticalmeasuressuch as Cronbach's Alpha and Pearson’scorrelation coefficient. The resultsindicatedthat the toolisreliable and valid for application, based on acceptable statisticalthresholds. The main findings of the studyrevealedthat: -There is a strongrelationshipbetween the level of instillingIslamiceducationwithin the family and the overalllevel of religiousupbringing. -There is a strongrelationshipbetween the methodsemployed by the family to instillIslamic values and the level of religiousupbringing in the child. -The parents' individualcharacteristics (such as age, educationallevel, and occupation) have a weakrelationshipwith the level of religiousupbringing. -The parents' individualcharacteristicsalso have a weakrelationshipwith the type of educationalmethodsused to instillIslamic values. -The family structure and the type of methodsfollowed show aweakrelationshipwith the level of Islamicupbringing. Keywords: Algerian family, Islamiceducation, educationalmethods, Islamic practices, level of religiousupbringing